Response of twelve soybean cultivars to water deficit in a Cerrados Dark-Red Latosol of the Federal District. II - evapotranspiration and water extraction - Espinoza, Waldo (Pesquisa Agropecuaria Brasileira, 2014)
A field study was conducted during the dry season of 1979 and 1980 at the Centro de Pesquisa Agropecuária dos Cerrados (CPAC/EMBRAPA) Planaltina, DF. Brazil to determine water use and to observe the capability of twelve soybean (Glycine max (L.) Merrill) cultivars to extract soil water when subjected to water stress. 'Doko' and 'Cristalina' cultivars when irrigated permanently showed values of total acumulated evapotranspiration of 650 e 604 mm respectively. Crop coeficient kc ranged from 0.3 at initial development stages to 1.0 at full vegetative stage and 0.45 at physiological maturity stage. Under water stress conditions it was not possible to separate cultivars in relation to its soil water extraction capability. Most of the cultivars showed a drastic reduction in water extraction 14-17 days after last irrigation. In general, 80% of soil water extracted was obtained from the upper 80cm of soil profile, which helps to explain why soybean crops are more resistant to water stress than corn or rice crops. Reductions in water extraction seems to be associated to low soil water potential observed in the upper soil layers. Considering that most of the soybean roots (75-85%) were found in the upper 20 cm of the soil profile, it is concluded that younger roots found in small amount below the soil 40 cm have a high soil water extraction efficiency.